The Influence of Business Model Canvas and Value Proposition Canvas on MSME Productivity: Structural Analysis Approach - Muhammad Khoirul Umam; Puteri Kamilla; W.Sigit Rahardjo; Ade Bani Riyan (Journal Research of Social Science, Economics, and Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in economic growth and employment in Indonesia; however, their productivity remains suboptimal due to limitations in business model design and the alignment of value propositions with market needs. This research aims to analyze the effect of the Business Model Canvas (BMC) and Value Proposition Canvas (VPC) on MSME productivity using a structural analysis approach. The research employs a quantitative explanatory method, using primary data collected from 161 MSME respondents via a Likert-scale questionnaire and analyzed with Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that both the Business Model Canvas and the Value Proposition Canvas have a positive and significant effect on MSME productivity, with effects partially and simultaneously. Business Model Canvas shows the most dominant influence, while Value Proposition Canvas enhances alignment between value offerings and customer needs. The model explains 78.8% of the variance in MSME productivity. These findings highlight that the integration of business models and value propositions is a key factor in improving productivity and competitiveness of MSMEs.